Psychological distress and its influencing factors in esophageal cancer patients undergoing radiotherapy: a longitudinal study - Li, Jin; Li, Xiaofan; Chen, Jue; Zhang, Ying; Yao, Ying; Yang, Huimin (Frontiers in Oncology, 2025)
ObjectiveTo investigate the dynamic changes of psychological distress and its influencing factors in cancer patients across different phases of radiotherapy.MethodsUsing a convenience sampling method, 226 esophageal cancer patients receiving radiotherapy at the Oncology Radiotherapy Center of a tertiary (Grade‐A) hospital in Henan Province were recruited from September 2022 to October 2023. Psychological distress was assessed using the Distress Thermometer (DT) at four time points: before the first radiotherapy session (T1), at the 15th session (T2), at the end of radiotherapy (T3), and one month after the completion of radiotherapy (T4). Generalized Estimating Equations (GEE) were utilized to analyze the factors related to psychological distress.ResultsAmong the 199 patients who completed the longitudinal follow-up, the mean psychological distress scores were 4.88 ± 1.63(T1); 5.09 ± 1.57(T2); 4.75 ± 1.56(T3); and 4.06 ± 1.57 (T4) respectively. GEE results indicated that age, monthly household income per capita, tumor stage, concurrent chemoradiotherapy, symptom burden, family support, and illness perception were influencing factors of psychological distress in esophageal cancer patients undergoing radiotherapy (P < 0.05).ConclusionEsophageal cancer patients exhibit moderate psychological distress during radiotherapy, with a trend of initial increase followed by a decrease as radiotherapy continues. Based on the changing characteristics and identified influencing factors, the healthcare team should develop dynamic and individualized intervention strategies to reduce patients’ psychological distress.